Sub-acute toxicity of Caladium bicolor (Aiton) leaf extract in Wistar rats - Omotoso, Dayo Rotimi; Brown, Ibifuro; Okojie, Itohan Grace (Journal of Phytology, 2020)
Herbal medicinal plants constitute an integral component of plant biodiversity whose application for therapeutic purposes has been a common practice since antiquity. However, studies have reported tissue pathologies following exposure to herbal medicinal plants or extracts. This study was carried out to assess the possible pathological effects of sub-acute exposure of methanol extract of Caladium bicolor on the hepatic histomorphology of experimental Wistar rats. Twenty four Wistar rats were divided into four groups A-D. Group A was administered with distilled water (2 ml/kg b.w) and groups B-D administered with 100 ml/kg, 200ml/kg and 300ml/kg b.w. of the extract respectively for twenty eight days. The bodyweight of experimental animals was recorded at regular intervals during the study period. After the treatment period, hepatic tissue was harvested, weighed and processed for histopathological study. The results showed that exposure to the extract causes significant (p<0.05) body and organ weight reduction, a significant increase in serum level of ALT and AST as well as prominent hepatic histopathological changes such as inflammation, necrosis and steatosis. Sub-acute exposure to methanol extract of C. bicolor thereby causes dose-independent hepatopathy in experimental animals. Hence, its application for therapeutic purposes needs to be re-evaluated and preferably discontinued to avoid these associated hepatic tissue pathologies.